Proton conductivity of modified polymeric membranes based on CsH₂PO₄ - Kungurtsev, Yurii E.; Ponomareva, Valentina Georgievna (Электрохимическая энергетика)
Comparative data on the effect of the heterogeneous nanodiamond additive on the protonconducting properties of polymer three-phase systems (CsH2PO4/fluoropolymer/nanodiamond) were obtained. Ultradispersed polytetrafluoroethylene and fluoroplast-42 (F-42) were used as fluoropolymers. It was shown that the introduction of small nanodiamond additives (fv = 0.6 vol.%) into the polymer electrolytes led to an increase in the superionic conductivity of hybrid systems due to the dispersion of salt, its partial amorphization and the more uniform distribution.